Treatment of Patients with Ankle Fractures (Literature Review) - N. I. Cherevatiy; L. N. Solomin (Acta Biomedica Scientifica, 2019)
The consequences of ankle fractures are a leading cause of disability among injuries of the musculoskeletal system. The problems of treating patients with this pathology have been of interest to researchers throughout the entire period of development of ankle joint surgery. However, numerous attempts to define terminology and classify chronic ankle joint injuries were unsuccessful. It can be argued that the consequences of ankle fractures are a symptom complex that includes traumatic deformity and pseudoarthrosis of the ankles, subluxation of the foot, contracture and arthrosis of the ankle joint. Today, for the surgical treatment of chronic injuries of the ankle joint, a number of surgical techniques are used, the indications and contraindications for each of them are not completely determined. In addition, longterm results are also the subject of a debate. There is a need to develop an improved approach to the treatment of the pathology under consideration, to create a decision-making algorithm in each specific clinical case. There is no doubt that preference should be given to organ-preserving operations.Based on a review of world literature, data were obtained on the epidemiology, medical and social significance of the effects of ankle fractures, and the evolution of researchers' views on the treatment of patients with this pathology and their development prospects were examined.